Peran Pengurus Asrama dalam Menangani Perilaku Maladjustment pada Santri Baru di Pondok Pesantren Roudlotut Tholibin Kota Probolinggo - Nisa, Karimatun; Suryadi (UIN Kiai Haji Achmad Siddiq Jember, 2024)
Maladjustment behavior refers to a state in which an individual is unable to adapt to their surrounding social environment, causing problems. The maladjustment behaviors observed in new students include reluctance to pray in congregation, skipping religious and formal school classes, and not participating in pesantren activities. The objectives of this research are: 1) to understand and describe how the dormitory supervisors handle maladjustment behaviors in new students at Roudlotut Tholibin Islamic Boarding School, 2) to identify and describe the factors causing maladjustment in new students at Roudlotut Tholibin Islamic Boarding School, and 3) to understand and describe the impact of the dormitory supervisors' efforts in managing maladjustment behavior on the adaptation of new students at Roudlotut Tholibin Islamic Boarding School. The research method uses qualitative with a descriptive type of research. Data collection techniques use observation, interviews, and documentation. Data analysis uses Miles & Huberman theory, namely data collection, data condensation, data presentation, and conclusion drawn. The results of this study indicate that the role of dormitory supervisors in handling maladjustment among new students is demonstrated by their well-executed duties and responsibilities. The factors causing maladjustment behavior in new students stem from personal issues within the pesantren and the significant distance between parents and students. The impact of the dormitory supervisors in managing maladjustment behaviors varies; some students successfully adjust, while others decide to leave the pesantren.